Longitudinal assessment of circulating insulin-like peptide 3 levels in healthy peripubertal girls - Hagen, Casper P.; Mieritz, Mikkel G.; Nielsen, John E.; Anand-Ivell, Ravinder; Ivell, Richard; Juul, Anders (Elsevier, 2015)
Objective: To elucidate the natural course of circulating insulin-like peptide 3 (INSL3) levels according to puberty as well as its relation to other reproductive hormones. Design: Population-based cohort study. Setting: Not applicable. Patient(s): Healthy peripubertal girls (n¼10) examined every 6 months; total number of examinations was 84; median (range) per girl:9 (4–10), including staging of pubertal breast development and blood samples. Intervention(s): None. Main Outcome Measure(s): Serum levels of INSL3, inhibin B, E2, antim€ullerian hormone, LH, and FSH (validated immunoassays), and T and androstenedione (liquid chromatography–tandem mass spectrometry). Result(s): Serum levels of INSL3 varied considerably between girls (range, 0.01–0.27 ng/mL) and within each girl as puberty progressed; intraindividual variation, median (range) 102% (65%–143%). Insulin-like peptide 3 increased in late puberty (B1 to B4þB5); geometric mean 0.03 ng/mL to 0.15 ng/mL. Insulin-like peptide 3 levels reflected markers of large follicles (T, androstendione, inhibin B, and E2) better than markers of small follicles (antim€ullerian hormone), and INSL3 staining was localized in theca interna cells of antral follicles. Conclusion(s): Insulin-like peptide 3 increased in late puberty, albeit inter- and intraindividual variations were substantial. Immunohistochemistry and intraindividual variation, as well as relations to other ovarian hormones, reveal that INSL3 in girls is a unique and specific marker of theca cells surrounding antral follicles. The potential clinical use of INSL3 for evaluation of ovarian function in girls remains to be elucidated.